Rancang Bangun Pengembangan Robot Pembersih Sampah Berbasis Internet of Thing (IOT) Untuk Pemantauan dan Pengontrolan Jarak Jauh. - MHD Micho Januar Prananta; Akim Manaor Hara Pardede; Melda Pita Uli Sitompul (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
The increasing waste problem requires innovative solutions that are efficient and sustainable. This study aims to design and build an Internet of Things (IoT) based garbage cleaning robot that can be monitored and controlled remotely. This system is designed by utilizing a microcontroller as the main brain, sensors to detect the presence of garbage, and an IoT-based communication module that allows monitoring and control of the robot via mobile devices or the web. Based on the results of the analysis and testing carried out, this study shows that the use of ESP8266 in the RC Trans Robot motor control with the Blynk application has succeeded in significantly increasing system efficiency. The system successfully responds to user input via a mobile application and can control the movement of the robot in real-time. The performance of the robot system controlled via a WiFi network shows good stability in various test scenarios. The robot can operate effectively within a distance that matches the range of the WiFi network, with fast control response and reliable communication.